Quantity Discrimination in Wolves (Canis lupus) - Utrata, Ewelina; Virányi, Zsófia; Range, Friederike (Frontiers in Psychology, 2012)
Quantity discrimination has been studied extensively in different non-human animal species. In the current study, we tested eleven hand-raised wolves (Canis lupus) in a two-way choice task. We placed a number of food items (one to four) sequentially into two opaque cans and asked the wolves to choose the larger amount. Moreover, we conducted two additional control conditions to rule out non-numerical properties of the presentation that the animals might have used to make the correct choice. Our results showed that wolves are able to make quantitative judgments at the group, but also at the individual level even when alternative strategies such as paying attention to the surface area or time and total amount are ruled out. In contrast to previous canine studies on dogs (Canis familiaris) and coyotes (Canis latrans), our wolves’ performance did not improve with decreasing ratio, referred to as Weber’s law. However, further studies using larger quantities than we used in the current setup are still needed to determine whether and when wolves’ quantity discrimination conforms to Weber’s law.